Corporate Social Responsibility of Islamic Banks: CSR website visibility, CSR initiatives, CSR strategy - Tahreem Noor Khan (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Purpose: The concept of Corporate Social Responsibility (CSR) has been widely known in the Islamic banking sector yet there is criticism and lack of trust which exists among stakeholdersDesign/Method/Approach: To reduce negative concern and to fill the gap in the literature, this research reinforces the integration of ethical and moral principles in the banking business.Findings: One of the integral and core elements of Islamic economics is ‘falah’; which focuses on wellness and the concept of reward in this world and hereafterOriginality/Values: To fulfil the needs of the ethical aspect of Islamic banks which leads to ‘falah’, this research has extracted the underlying theoretical issues of Islamic bank Corporate Social Responsibility (web visibility, initiatives, strategy). This research also determines the extent of CSR visibility in twelve leading Islamic banks’ corporate websites.